Attention allocation to multiple goals: The case of for‐profit social enterprises. (8th May 2014) - Stevens, Robin; Moray, Nathalie; Bruneel, Johan; Clarysse, Bart
<x xml:space="preserve">Abstract</x> The complexity of issues firms have to attend to make it impossible for CEOs to give their full attention to all issues concurrently. Drawing on the "attention‐based view" of the firm, this paper opens the black box of attention allocation in for‐profit social enterprises by showing how attention structures and the context in which the firm operates interplay. Utilizing empirical data on 148 for‐profit social enterprises, findings show that the attention structures—other‐regarding values, utilitarian identity, and resource availability—have a significant impact on the relative attention to social goals, while past firm performance as a context variable moderates these relations. Applying the principles of structural and situated attention, this paper makes an important contribution to management theory and attention allocation in for‐profit social enterprises. Copyright © 2014 John Wiley & Sons, Ltd.